Effect of spotters on state anxiety and self-confidence during maximal squatting among male high school athletes - Drew Rykert; Chad Harris; Kent J. Adams; Mark DeBeliso (Turkish Journal of Kinesiology, 2017)
The ideal performance state is manifested by psychological and physiological efficiency. The psychological effects of anxiety and self-confidence has been shown to alter the efficiency of performance. This study attempted to identify the state anxiety and self-confidence of high school athletes just prior to a one repetition maximum (1-RM) back squat and determine if the number of spotters affects an athlete's level of state anxiety and/or self-confidence. Male high school athletes (10th and 11th grades) were randomly separated into two experimental groups who performed the 1-RM back squat (BSQ) with either 1 spotter (1SG: n=52) or 3 spotters (3SG: n=54). Following a dynamic warm-up period and several progressive BSQ warm-up sets, and just prior to attempts at a 1-RM BSQ, the participants completed the revised Competitive State Anxiety Inventory-2 (CSAI-2R). The CSAI-2R included the number of spotters (1 or 3) that would be present during the subsequent 1-RM BSQ attempts. The CSAI-2R is a17-question instrument with three subscales (self-confidence, somatic anxiety, and cognitive anxiety). The subscale scores were compared between the 1SG and 3SG with an independent t-test (alpha≤0.05). None of the subscales (self-confidence, somatic anxiety, and cognitive anxiety) were significantly different between the 1SG and 3SG experimental groups (p>0.05). Within the parameters of this study, the number of spotters present during the execution of the 1-RM BSQ had no practical or statistical impact on self-confidence, somatic anxiety, and cognitive anxiety. Coaches and athletes could use this information in the training environment in order to make best use of personnel (assigned to spotting tasks), physical resources (ex. squat racks), and time management.